Tingkat Pengetahuan Komunitas Lansia di Posyandu Krajan Argosari Jabung Terhadap Neuropathy Perifer - M. Ariadika Al-kautsar; Dimas Sondang Irawan; Wendy Yuhardhika Marta Prabawati (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2025)
Introduction Elderly (elderly) is the final phase in human life marked by various changes in the anatomical structure and physiological functions of the body .Purpose: The outreach aims to provide education to the elderly regarding peripheral neuropathy, especially regarding its causes and how to do exercises independently at home to reduce the symptoms they experience. Therefore, the specific goal to be achieved is for the elderly to realize the importance of doing independent exercise at home in order to speed up recovery from the complaints they feel. Method: The methods used in Community Physiotherapy activities include counseling regarding definitions, symptoms, causal factors and physiotherapy management which can be carried out independently by the elderly. Before counseling, elderly people are asked to fill out a pre-test questionnaire to find out the extent of their understanding regarding peripheral neuropathy or tingling in the wrist and educate them on exercises and treatments that can be done at home to reduce complaints.Conclusion: The counseling carried out at the Posyandu for the Elderly in Krajan Argosari Village, Jabung, Malang, succeeded in providing knowledge and insight to the elderly regarding peripheral neuropathy. With this education, seniors are expected to be able to prevent and treat peripheral neuropathy independently through active exercise: